Narrative, meta-analytic, and systematic reviews: What are the differences and why do they matter? - Hodgkinson, Gerard P.; Ford, J. Kevin (Journal of organizational behavior, 2014)
This issue comprises the second IRIOP Annual Review Issue, following the incorporation of the International Review of Industrial and Organizational Psychology (IRIOP) into the Journal of Organizational Behavior (JOB). In this editorial, we highlight important differences between narrative, meta-analytic, and systematic review techniques and explain how each of these approaches to the reviewing of scholarly work has the potential to contribute to the continuing development of the IRIOP Annual Review Issue, as the leading outlet for the publication of critical, state-of-the-art overviews and commentary on established knowledge and developments at the forefront of the field. In so doing, we clarify further the sorts of contributions we are looking to publish, exemplified by the seven papers appearing in this second issue.